Artificial Intelligence in Islamic Family Law: An Ethical Analysis and Maqāṣid asy-Syarī'ah - Muhammad Sopiyan; Loso Judijanto; Maryam Asad; Saifudin Zuhri; Syufa’at Syufa’at (Universitas Muhammadiyah Bandung, 2026)
The development of Artificial Intelligence (AI) has brought a significant transformation in the provision of legal services, including in the field of Islamic family law. This research aims to analyze the working mechanism and regulation of AI systems in presenting the provisions of Islamic family law, identify the moral and ethical challenges it poses, and examine its conformity with the principles of maqāṣid asy-syarī'ah. This research uses a qualitative method with a literature study approach. Data is obtained from secondary sources in the form of scientific literature, regulations, and other relevant documents, which are then analyzed through descriptive-analytical techniques to construct normative and conceptual arguments. The results show that AI systems work through algorithm-based data processing designed to generate legal answers based on the compilation of legal sources and available databases. While it is able to improve the efficiency and accessibility of legal information, the use of AI in Islamic family law faces serious challenges in the form of algorithmic bias, potential privacy violations, the risk of autonomous decision-making without contextual considerations, and over-reliance on digital systems. From the perspective of maqāṣid as-syarī'ah, the use of AI has the potential to not fully realize the protection of religion, soul, intellect, descent, and property if it is not accompanied by adequate normative and ethical control. This study recommends the establishment of a regulatory framework and ethical guidelines based on maqāṣid ash-shari'ah that affirms the principles of accountability, algorithm transparency, and supervision of religious and legal authorities to ensure that the implementation of AI in Islamic family law remains in line with the values of justice and benefit.